Errors in the Use of Indonesian Spelling in Writing Open Spaces in the City of Pangkalpinang, Bangka Belitung - Lasmi Hartati; Hakim Prasasti Lubis (Raja Zulkarnain Education Foundation, 2025)
Open space writing in cities is often found on information boards, banners, and billboards used around the urban environment. Indonesian spelling errors that occur in these writings can affect public understanding and the image of the city itself. Therefore, this study aims to identify the types of Indonesian spelling errors that often occur in the writing of open spaces in Pangkalpinang City, Bangka Belitung. Several factors causing these errors include a lack of understanding of the applicable spelling rules by the public and those responsible for writing open spaces. In addition, inaccuracy in the editing and translation processes is also a significant factor in the emergence of these errors. Misuse of Indonesian spelling in the writing of open spaces in Pangkalpinang City, Bangka Belitung, is still quite common. Therefore, a joint effort is needed to increase public and open space managers’ understanding of the importance of correct language use, in order to create effective communication and improve the city’s visual image. This study uses a qualitative approach with descriptive methods. Data were obtained through direct observation of writing in various open spaces such as streets, parks, and other public areas in Pangkalpinang City. The author also conducted interviews with several parties involved in the creation and placement of written information in these open spaces. Data sources in this study include information boards, banners, and advertisements.